2019
DOI: 10.3390/healthcare7040127
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and Assessing Healthcare Organisational Culture in the England’s National Health Service: A Snapshot of Current Tools and Tool Use

Abstract: Healthcare Organisational Culture (OC) is a major contributing factor in serious failings in healthcare delivery. Despite an increased awareness of the impact that OC is having on patient care, there is no universally accepted way to measure culture in practice. This study was undertaken to provide a snapshot as to how the English National Health Service (NHS) is currently measuring culture. Although the study is based in England, the findings have potential to influence the measurement of healthcare OC intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…A case study approach [47,48] was adopted here to understand the deployment of a whole system change in the acute hospital along the four dimensions of STS outlined above. A case study is an approach that is used to generate an in-depth, multi-faceted understanding of a complex issue in its real-life context [49]. This case study sets out to address the question 'Was the deployment of LSS and person-centred care in this hospital a change on a whole system level?'.…”
Section: Case Studymentioning
confidence: 99%
See 2 more Smart Citations
“…A case study approach [47,48] was adopted here to understand the deployment of a whole system change in the acute hospital along the four dimensions of STS outlined above. A case study is an approach that is used to generate an in-depth, multi-faceted understanding of a complex issue in its real-life context [49]. This case study sets out to address the question 'Was the deployment of LSS and person-centred care in this hospital a change on a whole system level?'.…”
Section: Case Studymentioning
confidence: 99%
“…Simpson et al (2019) describe the importance of healthcare organisational culture when considering quality and patient safety in healthcare [49]. In 2014, the organisation culture was evolving from a "Power Culture" where the key to the organisation sits in the centre surrounded by widening circles of intimates and influence [61] (Handy 1999 p. 86).…”
Section: Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Then, the values were normalized. Finally, the RPN was found using Equation (2). The results are presented in Table 9.…”
Section: L16mentioning
confidence: 99%
“…Providing better hospital service quality is one of the most important issues in the modern healthcare industry [ 1 ]. The importance of healthcare services has been emphasized globally [ 2 , 3 ], where quality has been indicated as key to surviving in an extremely competitive environment [ 3 ]. At the end of the 20th century, many reports revealed that there must be a change to achieve high-quality levels of care while providing strong proof of evidence [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%